2019
DOI: 10.3390/cells8070643
|View full text |Cite
|
Sign up to set email alerts
|

Gas6 Prevents Epithelial-Mesenchymal Transition in Alveolar Epithelial Cells via Production of PGE2, PGD2 and Their Receptors

Abstract: The epithelial-mesenchymal transition (EMT) is important in organ fibrosis. We hypothesized that growth arrest-specific protein 6 (Gas6) and its underlying mechanisms play roles in the prevention of EMT in alveolar epithelial cells (ECs). In this study, to determine whether Gas6 prevents TGF-β1-induced EMT in LA-4 and primary alveolar type II ECs, real-time PCR and immunoblotting in cell lysates and ELISA in culture supernatants were performed. Migration and invasion assays were performed using Transwell chamb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 53 publications
(65 reference statements)
1
20
0
Order By: Relevance
“…13 Gas6 interaction with TAM modulates downstream signaling, involving various biological processes, including cell growth, migration, apoptosis, inflammation and epithelial-mesenchymal transition. 14,15 Gas6 can abrogate serum starvation-induced endothelial cell apoptosis via phosphorylation of the serine-threonine kinase Akt. 16 Moreover, Gas6 exhibits an attenuation of inflammation in multiple cell or animal disease models.…”
Section: Celastrol (Cel) Is a Pentacyclic Triterpene Bioactive Componmentioning
confidence: 99%
“…13 Gas6 interaction with TAM modulates downstream signaling, involving various biological processes, including cell growth, migration, apoptosis, inflammation and epithelial-mesenchymal transition. 14,15 Gas6 can abrogate serum starvation-induced endothelial cell apoptosis via phosphorylation of the serine-threonine kinase Akt. 16 Moreover, Gas6 exhibits an attenuation of inflammation in multiple cell or animal disease models.…”
Section: Celastrol (Cel) Is a Pentacyclic Triterpene Bioactive Componmentioning
confidence: 99%
“…The up-regulation of AXL causes the phosphorylation of Smad3, which is regulated by TGFβ signaling and is well correlated with an increase in the metastasis of cancer [43][44][45][46]. However it remains controversial whether AXL signaling is a positive regulator of EMT [47]. In this study we have shown that AXL activation is indispensable for TGFβ1 to promote EMT in NRK-52E renal tubular epithelial cells (Fig 7A-7C).…”
Section: Plos Onementioning
confidence: 57%
“…Next, we examined the contributions made by Axl and Mer signaling to Gas6-induced RhoA activity and HGF expression in LA-4 cells, using two kinds of Axl or Mer -specific siRNAs. LA-4 cells were transfected with either an Axl - or Mer -specific siRNA or a negative control siRNA and cultured for 48 h. With Axl or Mer protein knockdown (Figure S2A,B) [31], Gas6-induced RhoA activity in LA-4 cells was substantially suppressed (Figure 2A; Figure S2C). Concomitantly, the Gas6-induced increase in HGF expression levels was prevented by the silencing of either Axl or Mer RNA, at both the gene and protein levels (Figure 2B,C; Figure S2D,E).…”
Section: Resultsmentioning
confidence: 99%
“…However, the upregulation of HGF promotes carcinogenesis and EMT in hepatocellular carcinomas via AKT and cyclooxygenase-2 (COX-2) pathways [29,30]. Recently, we reported that Gas6 inhibits TGF-β1-induced EMT and signaling in lung epithelial cells, via the activation of Axl or Mer and the COX-2-dependent production of prostaglandin E 2 (PGE 2 ) and prostaglandin D 2 (PGD 2 ) [31]. Based on these findings, here we examined the role of the HGF-signaling pathway during the inhibitory effects of Gas6 on the EMT process, as well as during the inhibitory effects of Gas6 on the migration and invasion of LA-4 and primary mouse alveolar type II (AT II) epithelial cells.…”
Section: Introductionmentioning
confidence: 99%